Disability-Friendly Environment with Ramp: STEM Activity in Mathematics Classroom for Promoting Social Justice - Russasmita Sri Padmi; Titik Subarni; Farida Nurhasanah (Southeast Asian Mathematics Education Journal, 2022)
Mathematics is not only for educating functional members of society and producing a competent workforce but also for instilling social values and responsible citizenship. STEM is a potential learning approach to teaching social justice because it encourages students to integrate knowledge and skills from different subjects to solve real-life problems. This paper reports the first phase of design research to develop a STEM activity incorporating social justice issues for 8th-grade mathematics classrooms. The result of the first phase is a set of learning materials that integrates the subject content gradient in mathematics and simple machine in science in the context of designing an effective and efficient ramp for public use. The study confirmed that by designing in such a way that mathematics and science knowledge and skills are used in solving problems, social justice issues could be meaningful contexts for STEM lessons.